Shopping for Health: Seafood - Michelle Brown; Wendy J. Dahl (EDIS)
Seafood is part of the protein foods group of MyPlate and also provides other nutrients needed for good health. Because of the many health benefits, adults should consume at least eight ounces of a variety of seafood every week. Still, it is important to consider your budget when shopping for seafood. This 4-page fact sheet explains the health benefits of seafood and offers some money-saving strategies for making seafood more affordable. Written by Michelle Brown and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, April 2014. (Photo: Elena Gaak/iStock/Thinkstock)